Enforcing the pause: Transcription factor Sp3 limits productive elongation by RNA polymerase II - Valin, Alvaro (Landes Bioscience, 2013)
The transition of paused RNA polymerase II into productive elongation is a highly dynamic process that serves to fine-tune gene expression in response to changing cellular environments. We have recently reported that the transcription factor Sp3 inhibits the transition of paused RNA Pol II to productive elongation at the promoter of the cyclin-dependent kinase inhibitor p21(CIP1) and other Sp3-repressed genes. Our studies support the view that Sp3 has three modes of action: activation, SUMO-Sp3-mediated heterochromatin silencing and SUMO-independent inhibition of elongation. At the p21(CIP1) promoter, binding of the positive elongation factor P-TEFb kinase was not affected by Sp3. In contrast, Sp3 promoted binding of the protein phosphatase PP1 to the p21(CIP1) promoter, suggesting that Sp3-dependent regulation of the local balance between kinase and phosphatase activities may contribute to gene expression. Our findings show that the transition of paused RNA Pol II to productive elongation is an important step regulated by both promoter-specific activators and repressors to finely modulate mRNA expression levels.